Characterization of gamma-ray and neutron radiation absorption properties of synthesized quinoline derivatives and their genotoxic potential - Alaylar, Burak; Aygun, Bunyamin; Turhan, Kadir; Karadayi, Gokce; Sakar, Erdem; Singh, V. P.; Sayyed, M. I.; Pelit, Emel; Karabulut, Abdulhalik; Gulluce, Medine; Turgut, Zuhal; Isaoglu, Mine (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In this study, six different types of quinoline derivatives were synthesized, which can be used as an anti-radiation drug for active matter and its effects against radiation was determined. The effective removal cross-sections, mean free path, halfvalue layer and neutron transmission number were calculated for fast neutron radiation using the Monte Carlo simulation GEANT4 and FLUKA codes. Gamma radiation shielding parameters such as mass attenuation coefficient (MAC), effective atom number (Zeff), mean free path (MFP), exposure buildup factor (EBF) and halfvalue layer (HVL) were theoretically calculated using WinXCom and Phy-X/PSD software. Neutron equivalent dose measurements were performed using a 241Am-Be fast neutron source and a BF3 gas detector with 4.5 MeV of energy and 74 GBq activity. Both simulation and experimental measurements were compared with paraffin and conventional concrete. It was found that the quinoline derivative shielding material absorbed radiation much better than these reference materials. Additionally, the genotoxic potentials of the derivatives were assessed by using the yeast DEL assay and the results revealed that the derivatives can be considered genotoxically safe at the tested concentrations (up to 5 mM). It has been suggested that this new radiation shielding derivatives material can be used as active ingredients for a drug to be developed against both neutron and gamma radiation.
Keywords: Monte Carlo simulation; Quinoline derivatives; Gamma; Neutron; Drug; Chemistry; Nuclear Science & Technology; Physics